2014
DOI: 10.1002/2013jb010264
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simulation of the electromagnetic fields induced by the 2011 Tohoku tsunami

Abstract: The motion of seawater induces electromotive force of significant intensity due to Faraday's law, and the resulting electromagnetic (EM) field can be recorded by instruments installed on land or on the ocean bottom. However, few studies have successfully made a quantitative interpretation to obtain geophysical information from observations of tsunami-induced EM signals by an exact and accurate application of Maxwell equations. We built a scheme for three-dimensional numerical simulation to calculate EM fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…In this paper, we presented a new 3‐D time domain simulation method for the TGEM variations, adopting a vector FE method with unstructured tetrahedral mesh. Compared with the previous works (e.g., Zhang et al, ), our new simulation approach has the following four advantages: (1) realistic bathymetry representation using the unstructured mesh, unlike staircase‐type topography by structured meshes; (2) inclusion of the Earth's curvature; (3) capability of calculation of TGEM fields in broad areas with efficient mesh keeping required resolutions along coastlines and in the vicinity of observation points, which enables us to understand large‐scale TGE current circuits in the ocean; and (4) ability to simulate TGEM fields in time domain without any additional memory and computational complexity for FT and IFT. The accuracy of our 3‐D simulation method was examined using an analytical solution for a variety of tsunami wavelengths and ocean depths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we presented a new 3‐D time domain simulation method for the TGEM variations, adopting a vector FE method with unstructured tetrahedral mesh. Compared with the previous works (e.g., Zhang et al, ), our new simulation approach has the following four advantages: (1) realistic bathymetry representation using the unstructured mesh, unlike staircase‐type topography by structured meshes; (2) inclusion of the Earth's curvature; (3) capability of calculation of TGEM fields in broad areas with efficient mesh keeping required resolutions along coastlines and in the vicinity of observation points, which enables us to understand large‐scale TGE current circuits in the ocean; and (4) ability to simulate TGEM fields in time domain without any additional memory and computational complexity for FT and IFT. The accuracy of our 3‐D simulation method was examined using an analytical solution for a variety of tsunami wavelengths and ocean depths.…”
Section: Discussionmentioning
confidence: 99%
“…After the 2010 Chilean earthquake tsunami, Suetsugu et al (2012) investigated the seafloor TGM data consistent with ocean-bottom pressure (OBP) data observed in French Polynesia, while Manoj et al (2011) reported the TGM variations observed on Easter Island. As to the tsunami due to the 2011 off the Pacific coast of Tohoku earthquake (hereafter called the 2011 Tohoku tsunami), many reports on TGEM fields observed at the seafloor (Ichihara et al, 2013;Minami & Toh, 2013;Zhang et al, 2014) and on land (Tatehata et al, 2015;Utada et al, 2011) have been made. Since the TGM fields can be contaminated by magnetic variations of external origin, such as magnetospheric or ionospheric disturbances, the wavelet methods were introduced to reduce the difficulty in visual inspection for the TGM signals (e.g., Klausner et al, 2014;Schnepf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance for hazard mitigation are the TGEM fields associated with the leading part of the tsunami wave, hereafter referred to as the “first arrivals.” Although previous analytical solutions in the frequency domain are applicable to TGEM phenomena [e.g., Larsen , ; Tyler , ; Ichihara et al ., ], we do not have a general insight into EM variations at the seafloor associated with first arrivals of destructive tsunamis, because (1) the first arrivals are inherently transient and difficult to study in the frequency domain and (2) the effect of the ocean depth on TGEM fields has never been discussed in detail. For specific TGEM events, three‐dimensional (3‐D) time‐domain simulations may address these issues by following the recent developments in TGEM simulation techniques [e.g., Zhang et al ., ]. However, it will also be possible to understand basic characteristics of TGEM fields associated with tsunami first arrivals by combining analytical solutions in the frequency domain and two‐dimensional (2‐D) numerical experiments in the time‐domain [ Minami and Toh , ].…”
Section: Introductionmentioning
confidence: 99%
“…One was a magnetic signal associated with the 27 February 2010 earthquake (M8.8) off the coast of Chile, which was observed at Easter Island, 3500 km from the epicenter (Manoj 2011). A magnetic signal associated with the tsunami caused by the 11 March 2011 Tohoku earthquake (M9.0) was observed in Chichijima Island, from which a clear signal of the oceanic dynamo effect was reported by Zhang et al (2014b). They reproduced the observed magnetic field but did not perform a comparison between the tsunami and the magnetic field.…”
Section: Introductionmentioning
confidence: 94%
“…Ichihara et al (2013), Sugioka et al (2014), and Minami et al (2015) described a more extended formulation using a seafloor with finite electrical conductivity. Zhang et al (2014b) considered the electrical conductivity of the seafloor as a threedimensional multi-layer structure. However, Tada et al (2014) showed that the electrical conductivity of the seafloor is less than 0.1 S⁄ m around Chichijima Island.…”
Section: Appendixmentioning
confidence: 99%